Mines in the End Zone: Are there Downsides to Team Performance?. (20th November 2020) - Mumford, Troy V.; Maynard, M. Travis
Abstract: Research on teams in organizations tends to focus on understanding the causes of team performance with a focus on how to enjoy the benefits of team success and avoid the negative consequences of team failure. This paper instead asks the question, 'what are some of the negative consequences of team success?' A review of the literature on teams is augmented with research from cognitive science, sociology, occupational psychology, and psychology to explore the potential negative long-term consequences of teamwork success. The general topics of groupthink, overconfidence bias, regression to the mean, role overload, and strategy calcification are reviewed while discussing the implications for future research streams and practical team management.